"I think you're probably given the client that...you need" Identifying valent encounters within client/clinician interactions: An Interpretative Phenomenological Analysis - Reynolds, Niamh (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2025)
Client/clinician interactions are viewed as an integral component and facilitator of healthcare practice globally. However, there is currently a paucity of literature regarding relational aspects of healthcare practice. Of the research that does exist relating to the relational aspects of healthcare, much of the research relates to placing the clients' needs at the centre of practice, with little reference to the role of the clinician in the context of co-constructed client/clinician interactions. This research study aims to provide a further level of understanding regarding the role of the clinician in these interactions by exploring the meaning and significance of clinicians' experiences of client/clinician interactions in health and social care profession (HSCP) practice. This study employs the use of a multiple perspective interpretative phenomenological analysis (IPA) research design to explore HSCP clinicians' understandings and experiences of client/clinician interactions. IPA affords the researcher the opportunity to access, understand and engage with the reflections of the clinician in the context of their significant lived experiences of client/clinician interactions. This engagement was achieved through the researcher's commitment to being cognisant of and adhering to the theoretical underpinnings and core principles of IPA research to include phenomenology, idiography, and hermeneutics. Data was collected from a series of online focus groups, as a means of exploring clinicians' experiences and understandings of client/clinician interactions. Participants were recruited from five professions within social and therapeutic domains of HSCP specifically occupational therapy, physiotherapy, play therapy, social work, and speech and language therapy. In summary, my research identified the construct of valent encounters within HSCP practice. The findings of my study suggest that clinicians attribute a valent quality to particular client/clinician interactions, as described via three discrete general experiential themes (GETs) in my research study. GET I describes the Clinician as having been elevated by the client. This theme describes the ways in which valent encounters with clients have raised clinicians to a higher order of professional and personal insight. Secondly, GET II of Clinician as having been enrooted by the client reflects upon how valent encounters with clients have anchored and grounded clinicians in the context of clinical practice while also instilling a commitment to continually consider the nature, essence, and expectations of the clinical role. Finally, GET III of Clinician as having been emboldened by the client reflects upon how valent encounters with the client instil within the clinician a courage to trust and believe in the capacity of potential despite changeable conditions of clinical practice. The findings of the study can be nestled within and extend existing concepts and theories as related to both HSCP literature and psychotherapy literature. Additionally, the findings of the research both complements and adds to existing theoretical constructs in the HSCP and psychotherapy literature base. Furthermore, potential implications of the findings for clinical practice include recognising and embracing valent encounters in clinical practice, increased acknowledgement of the central role of the client in healthcare practice, and the promotion of preventative education and training in undergraduate HSCP students. The limitations and future directions of this research are also discussed. For example, the findings of the study may not be representative of all HSCP but rather relate to specific social and therapeutic domains of HSCP. Additionally, information relating to participants' years of clinical experiences and participants' place of work was not systemically collected as part of recruitment/data collection process. Meanwhile, future studies may wish to explore clients' experiences and understandings of valent encounters, as well as the context in which valent encounters are created and facilitated in clinical practice.
APPROVED
Keywords: clinician; client/clinician interaction; therapeutic alliance; health and social care professions; person-centred care; client; interprofessional practice; multiple perspective interpretative phenomenological analysis; compassion satisfaction; compassion fatigue; reflective practice